Sains dan Teknologi dalam Ketamaduan Islam: Analisa Epistemologi dan Metodologi - Moch Holil; Zainul Bakir Fauzi; Alfina Wildatul Fitriyah (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
Science and technology have developed along with human development in this universe. The history of human civilization requires efforts to manifest values ​​within the scope of their own perspective. The above facts can be proven with strong support for the purposes of science and technology itself, these are values ​​and include cultural views formed by humans themselves.